El fallo en el proceso de impugnación de la paternidad ante la negativa del demandado a realizarse el examen de ADN. - Chimbo Sisa Edison Fabián (2024)
Paternity challenge is a legal process by which a person's assigned paternity of a child is questioned. This procedure may be initiated for a variety of reasons, such as doubts about the biological relationship between the alleged father and the child, or the presence of new information that questions established paternity. DNA testing, also known as paternity testing or genetic testing, is a method used to determine the biological relationship between an individual and a potential son or daughter. This test is highly accurate and is commonly used in paternity legal cases to confirm or rule out that a person is the biological father of a child. DNA paternity testing is usually performed by taking a DNA sample from the alleged father and the child, often obtained through an oral swab or blood sample. These samples are analyzed to compare specific genetic markers; Humans have thousands of such markers, and the combination of these can uniquely identify each individual (with the exception of identical twins). DNA analysis looks for matches on Short Tandem Repeat markers, which are short sequences of DNA that repeat in the human genome. In paternity testing, the STRs of the alleged father and the child are compared, and if there are enough matches, the result strengthens the claim of a paternity relationship. Paternity rates and probability of paternity are calculated based on matches of these markers. A defendant's refusal to take a DNA test in a paternity challenge process can have significant legal implications. If a defendant refuses to take a DNA test, the court may interpret that refusal as evidence against that person. and sometimes it can lead to the presumption of paternity, although this is not always automatic and depends on the judge's criteria since this situation is not properly legislated in the Civil Code. Keywords: paternity challenge, DNA test refusal.